Trauma and Sex Surveys Meet Minimal Risk Standards - Yeater, Elizabeth; Miller, Geoffrey; Rinehart, Jenny; Nason, Erica (Psychological Science, 2012)
Institutional review boards assume that questionnaires asking about “sensitive” topics (e.g., trauma and sex) pose more risk to respondents than seemingly innocuous measures (e.g., cognitive tests). We tested this assumption by asking 504 undergraduates to answer either surveys on trauma and sex or measures of cognitive ability, such as tests of vocabulary and abstract reasoning. Participants rated their positive and negative emotional reactions and the perceived benefits and mental costs of participating; they also compared their study-related distress with the distress arising from normal life stressors. Participants who completed trauma and sex surveys, relative to participants who completed cognitive measures, rated the study as resulting in higher positive affect and as having greater perceived benefits and fewer mental costs. Although participants who completed trauma and sex surveys reported slightly higher levels of negative emotion than did participants who completed cognitive measures, averages were very low for both groups, and outliers were rare. All participants rated each normal life stressor as more distressing than participating in the study. These results suggest that trauma and sex surveys pose minimal risk.